A shear-dependent NO-cGMP-cGKI cascade in platelets acts as an auto-regulatory brake of thrombosis - Lai Wen (Nature Portfolio, 2018)
Nitric oxide (NO) inhibits thrombosis in part by stimulating cyclic guanosine monophosphate (cGMP) production and cGMP-dependent protein kinase I (cGKI) activity in platelets. Here, Wen et al. develop a cGMP sensor mouse to follow cGMP dynamics in platelets, and find that shear stress activates NO-cGMP-cGKI signaling during platelet aggregation to limit thrombosis.